2022
DOI: 10.1002/pc.26555
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical studies on low‐velocity impact damage of composite laminates toughened by nickel‐coated carbon fiber veil

Abstract: The low‐velocity impact response of carbon fiber composite laminates toughened by nickel‐coated carbon fiber (NiCF) veil interleaves was investigated experimentally and numerically. The experimental results indicated that the impact resistance of laminates with a layer of NiCF veil of 34 g/m2 inserted in the midplane was improved, especially in terms of increased peak impact force and residual compressive strength (by 16.15%), and reduced damage area (by 30.92%). The enhancement mechanisms were attributed to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…The damage energy absorbed by the specimen can be determined by integrating the suddenly decreasing part in the load-displacement curve, which is displayed in the form of shaded areas in Figure 6. The damage energy absorption ratio r 1 can be calculated by Equation (1).…”
Section: Impact Response Of Various Laminatesmentioning
confidence: 99%
See 2 more Smart Citations
“…The damage energy absorbed by the specimen can be determined by integrating the suddenly decreasing part in the load-displacement curve, which is displayed in the form of shaded areas in Figure 6. The damage energy absorption ratio r 1 can be calculated by Equation (1).…”
Section: Impact Response Of Various Laminatesmentioning
confidence: 99%
“…Carbon fiber reinforced polymers (CFRPs) can realize outstanding mechanical performance in a wide range of applications; however, they are sensitive to normal impact stress. [1][2][3] CFRPs do not provide negligible warning when they undergo material failure during their service life because a fracture only results in low deformation. 4 In contrast, nacre from mollusk shells shows high strength and hardness, and it exhibits good toughness because of its three-dimensional "bricks and mortar" structure, as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results show that fiber hybridization has a significant positive effect on impact resistance, and the sharpness of the impactor can affect peak force, damage area, and energy absorption. Jia et al [ 17 ] studied the carbon fiber composite laminates toughened by nickel‐coated carbon fiber (NiCF) veil interleaves, and the experimental results indicated that the impact damage area decreased by 30.92%, and the residual compressive strength increased by 16.15%. Zhao et al [ 18 ] carried out high‐velocity impact experiments on three types of composite plates, and compared the out‐of‐surface deformation, failure mode, and energy dissipation of different stacking sequences.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Nanoclays in conjunction with conductive fillers and nickel-coated fibers were used to increase the electrical conductivity of polymer composites. [9] Liu et al [10,11] incorporated nickel-coated carbon fiber veils in composite laminates, which improved the impact resistance and interlaminar fracture toughness (G IC , G IIC ), explained by additional energy dissipation through fiber pull-out breakage and peeling of the nickel coating. Ni-coated fiber composites have increased electromagnetic-wave absorptivity, which encourages their use in such applications as radar stealth, [12][13][14][15][16][17][18][19][20][21] interference shielding, [5] and microwave heating.…”
Section: Introductionmentioning
confidence: 99%